Malignancy in ankylosing spondylitis: a cross-sectional analysis of a large population database - Mohamad Bittar; Sali Merjanah; Reem Alkilany; Marina Magrey (BMC Rheumatology, 2022)
Abstract Background Increased cancer-risk has been reported with rheumatoid arthritis and systemic lupus erythematosus, but the risk is poorly studied in ankylosing spondylitis (AS). Conflicting data in AS have been reported in Asia and Europe, with lack of US population-based studies. Our objective is to study the prevalence of cancer in patients with AS in the US. Methods Using the Explorys database, we performed a cross-sectional study. Data from AS patients and controls were stratified by 2 rheumatology visits, age groups, clinical characteristics, and frequency of cancers. The data were analyzed using a series of chi-square tests of independence as well as logistic regression to test for association between AS and cancer. Results 1410 AS patients (12.88%) had cancer. Female AS patients had a lower prevalence of cancer compared to controls (OR 0.840, 95% CI [0.769, 0.916]), while male AS patients had no statistically significant difference (OR 1.011, 95% CI [0.929, 1.099]). Among patients with AS, Skin cancers (squamous cell, malignant melanoma, and basal cell) and head and neck cancers were significantly increased. Conclusion Our study demonstrated that the prevalence of “any-type-cancer” was not increased in AS patients compared to controls with no rheumatic disease. Skin, head, and neck cancers were more frequently seen in AS patients.